THE COGNITIVE NEUROSCIENCE OF RELIGIOUS BELIEF FROM THE PERSPECTIVE OF SAM HARRIS: A CRITIQUE - M.Salih, Amad Kadhim; Ali, Ismael (Universitas Islam Negeri Ar-Raniry, 2025)
This research aims to criticize the perspective of Sam Harris on which he built his philosophical and intellectual framework in his cognitive neuroscience-based interpretation of multiple philosophical concepts such as belief, disbelief, morality, and free will in his base research paper titled (Functional Neuroimaging of Belief, Disbelief, and Uncertainty). This research relied on description, analysis, and criticism. It describes Sam Harris’s core thoughts in his study on neuroimaging, and then analyzes them and states their purposes and implications. Then it criticizes his ideas, relying on two elements. First, the logical and philosophical and Kalam argumentations to criticize his ideas and to explain the flaws in his knowledge foundations. Second, relying on the neuroscientists’ views contradicting the theses in Harris’ paper besides general scientific criticism. The research concluded that consciousness precedes matter and not the opposite, and that belief is innate in the human mind from birth and is one of the so-called necessary-knowledge that cannot be refuted by material experiences. Thus, faith is an innate awareness and not a purely materialistic cognitive state that can be reduced, or abstracted, and its level cannot be measured by simply conducting tests through belief, disbelief, or uncertainty about written prepositions.